2016
DOI: 10.1051/shsconf/20162601088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of virtual chemistry laboratory instruction on pre-service science teachers’ scientific process skills

Abstract: Abstract. This study aimed to investigate the impact of virtual chemistry laboratory instruction on pre-service science teachers' scientific process skills. For this purpose, eight laboratory activities related to chemical kinetic, chemical equilibrium, thermochemistry, acids-bases, and electrochemistry were developed. Those activities were performed in virtual laboratory environment by the pre-service teachers in the experimental group and in the real laboratory environment by c the preservice teachers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…For instance, Yang and Heh (2007) found that high school students who used the virtual laboratory enhanced their science process skills significantly higher than the students in the hands-on laboratory. A study by Mutlu and Acar-Şeşen (2016) also supported this result. They reached the conclusion that the virtual laboratory environment provided pre-service science teachers with the opportunity to develop their science process skills significantly better than the handson laboratory environment.…”
Section: Comparison Of Different Laboratory Environments Concerning C...supporting
confidence: 53%
“…For instance, Yang and Heh (2007) found that high school students who used the virtual laboratory enhanced their science process skills significantly higher than the students in the hands-on laboratory. A study by Mutlu and Acar-Şeşen (2016) also supported this result. They reached the conclusion that the virtual laboratory environment provided pre-service science teachers with the opportunity to develop their science process skills significantly better than the handson laboratory environment.…”
Section: Comparison Of Different Laboratory Environments Concerning C...supporting
confidence: 53%
“…Interpretation skills include interpreting the results of observations by recording the results of observations separately between main and side results, connecting observations, finding patterns and regularities from observation, and concluding (Franco, 2016;Ohn & Ohn, 2020). Hypothetical skills enable student to stating between two variables or proposing an approximate answer to an event (Mutlu & Şeşen, 2016). Experiment planning skills constitutes a series of activities planning activities, including determining experimental variables, determining activity objects, and work steps.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental skills include the skills to carry out experimental steps to data processing (Mutlu & Şeşen, 2016;Oktiawan et al, 2019). Communicating skills are those skills that are both verbal and written in order to convey knowledge accurately and precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Recent empirical studies that addressed virtual laboratories have confirmed a significant impact in enhancing the practical skills and achievement of knowledge for target learners in various fields of science across educational stages. Examples include the physicsrelated academic achievements and process skills of tenth graders (Yang & Heh, 2007), undergraduate students' conceptual understanding of electric circuits (Zacharia, 2007), conceptual knowledge regarding electric circuits and procedural skills of secondary vocational engineering education (Kollöffel & de Jong, 2013), undergraduate students' photoelectric concepts (Bajpai, 2013), elementary school students' science learning (Sun, Lin, & Yu, 2008), conceptual understanding and science process skills of fourth grade primary school students (El-Sabagh, 2011), high school students' achievement levels and attitudes towards chemistry (Tüysüz, 2010), seventh grade elementary pupils' knowledge regarding chemical topics (Herga & Dinevski, 2012), scientific process skills related to chemistry for first grade pre-service science teachers (Mutlu & Şeşen, 2016).…”
Section: Introductionmentioning
confidence: 99%